Kids online : opportunities and risks for children - Livingstone, Sonia M.; Haddon, Leslie (Bristol, U.K. ; Portland, OR : Policy Press, 2009)
Section I - Researching European children online: What we know, what we don't know -- Research with children -- Opportunities and pitfalls of cross-national research -- Cultures of research and policy in Europe -- Section II - Going online: new opportunities?: Opportunities and benefits online -- Adolescents and social network sites: identiy, friendships and privacy -- Young people online: gender and age influences -- Digital divides -- Section III - Going online: new risks?: Risky contacts -- Inappropriate content -- Problematic conduct: juvenile delinquency on the internet -- Children and the internet in the news: agency, voices and agendas -- The role of parental mediation in explaining cross-national experiences of risk -- Section IV - Policy implications: Maximising opportunities and minimising risks for children online -- Parental mediation -- Making use of ICT for learning in European schools -- Media literacy.